Applying trauma-sensitive practices in school counseling : interventions for achieving change - Rawson, Stacey (New York, NY : Routledge, 2020)
"Applying Trauma-Sensitive Practices in School Counseling is an essential text for school counselors who need the research, knowledge, and skills to intervene and positively impact the educational outcomes for students with trauma. This practice-based guide begins with Adverse Childhood Experiences (ACEs). Through case studies and current research, school counselors will learn how trauma effects brain development, social-emotional development, behavior, and academic learning for children and adolescents. The research in the first section leads to a variety of trauma-sensitive strategies for school counselors in the second section. Included are trauma-informed programs that school counselors can implement school-wide, along with tools and strategies school counselors can apply in personal practice. Case studies of students with ACEs who improved behaviorally or academically due to school counseling interventions demonstrate the effectiveness of the tools offered in the text With up-to-date information about chronic stress in childhood and practical strategies that can be adapted and implemented, this guidebook is crucial for school counselors, especially those who support students with ACEs"--
The ACEs Study : Lasting Effects from Childhood Trauma -- Neurobiology and Learning : How Trauma Changes the Developing Brain -- Mental Health: What's Beneath the Symptoms -- The Role of a Trauma-Sensitive School Counselor -- Trauma-Sensitive Schools : Reframing the "Why" not the "How" -- Schoolwide Programs that Align with a Trauma-Sensitive Philosophy -- Developing TSC -- Tiered Interventions : Putting It All Together -- Self-Regulation : Developing Strategies Through Skill-Building Lessons -- Creating Connectedness : Caring Matters -- Conclusion : Next Steps for Counselor Leaders.
OCLC-licensed vendor bibliographic record.
Keywords: Educational counseling; School mental health services; Psychic trauma in children; Psychic trauma in adolescence; PSYCHOLOGY / Psychotherapy / Child & Adolescent